Pendekatan Multidisipliner dalam Pendidikan Islam untuk Menghadapi Dinamika Hukum Syariah Modern - Nur Azka Wahida; Berliana Setyaningrum; Ahmad Lutfi Abdillah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The development of modern sharia law requires a multidisciplinary approach to education. This article examines how Islamic education can utilize various disciplines, such as technology, economics, and social sciences, to support a contextual understanding of sharia law. This study also highlights the challenges and opportunities in developing an Islamic education model that is able to face the changing times.